Using Apps to Enhance Students' Learning of English Vocabulary - Albarakati, Hassan (My University, 2019)
Nowadays, education in the Kingdom of Saudi Arabia is entering a new phase (Saudi Vision 2030), which focuses on quality of education, ensuring that students are being prepared to deal with future challenges such as cultural diversity, economic changes, and globalization. Because of English becoming more important under the trend of globalization and internationalization, it is considered to be one of the most important foreign languages in Saudi Arabia. Teaching and learning a foreign language through technology has become a new trend in foreign language education all over the world (Liu, 2009). Hence, technology integration in our classrooms has become an important aspect of successful teaching. I find that many students are demotivated to learn English language because they do not realize the advantage of learning it. Therefore, EFL students in Saudi Arabia often struggle with literacy and vocabulary retention, which also affects their grammar learning and reading comprehension. As a result, I presume that this project will be a good opportunity to take advantage of students' interests in technological tools, such as cell phones apps, in order to help increase students' vocabulary and trigger their desire to learn the language. However, I intend to implement this project with the seventh-grade students at Al-Ghuzayat Middle School in Al-Jamoum, Makkah, Saudi Arabia, by using two apps: Duolingo and Kahoot in a period of 12 weeks so that I can evaluate the effects of learning vocabulary through these two apps by taking a pretest, a posttest, and a survey at the end.
Keywords: Applications; Software Application; Vocabulary; English Language; Duolingo; Kahoot; Technology; Student learning; Smartphone applications